Eficacia clínica del uso de metildopa em gestantes con antecedentes de hipertensión crónica en EsSalud III-Iquitos, 2021 - Manuyama Solsol, Andy Martin (2022)
Conical hypertension affects 1 to 5% of all pregnancies, the clinical approach to achieve adequate pressure management is still debatable. There are few cases of chronic hypertension with pregnancy-induced hypertension with a serious prognosis. Severe hypertension must be treated, but when this hypertension is mild or moderate (140-159/90-109 mm Hg); In addition, other factors other than just blood pressure measurement should be considered, such as comorbidities, gestational age at delivery, among others. It remains unclear how hypertensive treatment reduces the risk of maternal and fetal morbidity and mortality and should be the goals of antihypertensive treatment. Likewise, the benefits of treatment in women without proteinuria. This research project presents as a formulation of the problem: What is the clinical efficacy of Methyldopa in pregnant women with a history of chronic hypertension in EsSalud III Iquitos? General Objective: To evaluate the clinical efficacy of Methyldopa in pregnant women with a history of chronic hypertension in EsSalud III Iquitos. Methodology: A quantitative study will be carried out, according to the intervention of the experimental researcher controlled according to the scope to demonstrate a causal relationship: analytical, according to the number of measurements of the casecontrol study variable and according to the data collection planning: prospective. A randomized study to evaluate the clinical efficacy of Methyldopa in pregnant women with a history of chronic arterial hypertension in EsSalud III of Iquitos. Population: the study will consist of 100 pregnant women with a history of chronic arterial hypertension in a period of one year, who will be divided into 2 groups of 50 pregnant women and differentiated treatment will be initiated in each group: Group 1: Pregnant women with a history of chronic arterial hypertension who start treatment with Methyldopa at a dose of 250 mg every 8 hours after 20 weeks of gestation or birth and Group 2: Pregnant women with a history of chronic arterial hypertension who start treatment with Methyldopa at a dose of 1 g every 12 hours after 20 weeks gestation or birth.